2017
DOI: 10.1084/jem.20170600
|View full text |Cite
|
Sign up to set email alerts
|

Short Aβ peptides attenuate Aβ42 toxicity in vivo

Abstract: Data demonstrate that short amyloid-β (Aβ) peptides are not toxic in vivo and can partially block toxicity associated with Aβ42 accumulation. Moore et al. further validate the use of γ-secretase modulators that lower Aβ42 and increase short Aβs as potential Alzheimer’s disease therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 69 publications
(92 reference statements)
6
66
0
Order By: Relevance
“…4A). In contrast, and consistent with our previous observations [44], a single copy of the Aβ42 WT induced a more aggressive phenotype characterized by disorganization, ommatidial fusion and partial lack of bristles (Fig. 4A).…”
Section: Neurotoxic Assessment Of Mutant Aβ Peptides In the Drosophilsupporting
confidence: 93%
“…4A). In contrast, and consistent with our previous observations [44], a single copy of the Aβ42 WT induced a more aggressive phenotype characterized by disorganization, ommatidial fusion and partial lack of bristles (Fig. 4A).…”
Section: Neurotoxic Assessment Of Mutant Aβ Peptides In the Drosophilsupporting
confidence: 93%
“…These peptides have 3 different specific amino acids that could modify the human peptides ability to form toxic aggregates or oligomers. Different combinations of Aβ peptides are known to interfere with the rate of formation of aggregates/oligomers as well as their structural type [71]. This is consistent with the possibility that shorter Aβ40 peptides (or sequence divergent rodent peptides) could prevent toxicity of Aβ42 in rodent models.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, overexpression of the phosphomimetic Ab42 S8E resulted in sparse deposits, with very low levels of both SDS-soluble and FA-soluble Ab42, whereas nonphospho-mimetic Ab42 S8A exhibited increased deposits, suggesting that phosphorylation does not play a signi cant role in Ab42 deposition. We have previously shown that overexpression of WT Aβ40 resulted in no amyloid pathology [44]. However, when a series of BRI2-Aβ40 mutants were overexpressed in the neonatal brain, we observed that Aβ40 E22G and E22Q/D23N aggregated and accumulated in the brain (Fig.…”
Section: Resultsmentioning
confidence: 75%